Low-temperature deuterium annealing to improve performance and reliability in a MOSFET. (November 2022) - Yu, Ji-Man; Wang, Dong-Hyun; Ku, Ja-Yun; Han, Joon-Kyu; Jung, Dae-Han; Park, Jun-Young; Choi, Yang-Kyu
Highlights: Low-temperature deuterium (D2 ) annealing (LTDA) to improve performances and reliability of a MOSFET. Reducing a thermal budget especially in the backend-of-the-line (BEOL). Quantitative analysis for improvement of electrical performance. Profiling of D2 by secondary ion mass spectrometry (SIMS). Abstract: Low-temperature deuterium (D2 ) annealing (LTDA) is applied to improve performances and reliability of a MOSFET. The LTDA is performed at 300 °C, which is at least 100 °C lower than the widely used temperature of forming gas annealing (FGA) with H2, which contributes to reducing a thermal budget especially in the backend-of-the-line (BEOL). DC performances, such as subthreshold slope ( SS ), threshold voltage ( V TH ), and on-current ( I ON ) were statistically compared in cases with and without the LTDA to evaluate their improvements. Profiling of D2 by secondary ion mass spectrometry (SIMS) supports that D2 can permeate a gate oxide and passivate dangling bonds and traps near the interface of the SiO2 -Si channel. Therefore I ON, SS, and V TH were improved, gate leakage current ( I G ) was reduced, and immunity to positive bias stress (PBS) became better.